Comprehensibility and impact of vehicle dashboard indicator light symbols on drivers' preventive maintenance compliance. - Charles Atombo; Maxwell Selase Akple; Arnold Dumenya; Paul Adzimahe (PLoS ONE)
Background Dashboard indicator light symbols convey information about vehicles status and functioning, but action taken to address issues associated with these symbols depend on drivers' familiarity and comprehension of the symbols as well as demographic factors. Thus, this study assesses drivers' familiarity and comprehension of dashboard indicator light symbols and further examines the impact of driver background factors and comprehension level of the symbols on drivers' preventive maintenance compliance. Method Through a survey involving 2530 drivers, familiarity and comprehension of 25 dashboard indicator symbols used on most vehicles were collected. Descriptive analysis and Generalised Ordered Logistic Regression were used to analyse the data. Results Indicator light symbols that recorded a higher percentage of familiarity and were deemed appropriate were comprehended by most drivers. Symbols with pictorial signs were better understood. Overall, there were substantial significant differences among symbols in drivers' familiarity and comprehension. Regression analysis indicates that the majority of dashboard indicators with low comprehension had a positively significant relationship, while symbols with better understanding recorded a negative relationship with driver's preventive maintenance compliance. However, symbols such as tyre pressure, traction, 4*4 active, and power steering warning lights, which were poorly comprehended, showed a negative significant association with preventive maintenance compliance. Conclusion The complex relationship between comprehension and drivers' preventive maintenance compliance underscores the importance of including driver education programs and symbols standardisation to improve comprehension and preventive maintenance compliance, promoting road safety and vehicle reliability.